Islamic Spiritual Counseling Approaches: Building the Values of Character Education through Ta'alluq, Takhalluq and Tahaqquq Methods - Isa, Nor Junainah Mohd; Utomo, Prio (Program Studi Bimbingan dan Konseling Islam, 2024)
The problem of character today is that there is still little integration of religious concepts as a shaper of human character. This study aims to determine the values of character education using a psychosufistic (Sufism) approach through ta'alluq, takhalluq, and tahaqquq methods. The research design used a qualitative-descriptive approach (hermeneutics). Data collection used primary and secondary data sources of Sufism texts (kitab-kitab). Data analysis used hermeneutic-psychosufistic analysis. The results showed that the teaching values that can be built in shaping human character include (1) the value of sincerity, (2) the value of willingness, (3) the value of patience, (4) the value of humility, (5) the value of tawakal, (6) the value of hope, (7) the value of fear, (8) the value of gratitude. This research contributes as enrichment material and human teachings about the procedures for growing character values (personality) by emphasizing spiritual management exercises using a psychosufistic (Sufism) approach through the ta'alluq, takhalluq, tahaqquq methods.